1965
DOI: 10.1017/s0022112065001635
|View full text |Cite
|
Sign up to set email alerts
|

On some aspects of fully-developed turbulent flow in rectangular channels

Abstract: For fully-developed turbulent flow in straight channels of non-circular cross-section, there exists a transverse mean flow superimposed upon the axial mean flow. This transverse flow, commonly known as secondary flow, interacts with the axial mean flow and turbulence structure in a complex manner. In this paper several heretofore unexplored aspects of this type of secondary flow are discussed on the basis of results of an extensive experimental programme which was conducted for steady, incompressible, fully-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0
3

Year Published

1968
1968
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(83 citation statements)
references
References 6 publications
(3 reference statements)
10
70
0
3
Order By: Relevance
“…The computations by Nakayama, et al (1983) are based on the algebraic stress model developed by Launder & Ying (1972). It can be seen here that the present model agrees with the experimental results of Gessner and Jones (1965) in the sense that it also exhibits weaker secondary flow velocities near the center of the duct. The computations were then extended to flow in curved ducts.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The computations by Nakayama, et al (1983) are based on the algebraic stress model developed by Launder & Ying (1972). It can be seen here that the present model agrees with the experimental results of Gessner and Jones (1965) in the sense that it also exhibits weaker secondary flow velocities near the center of the duct. The computations were then extended to flow in curved ducts.…”
Section: Resultssupporting
confidence: 83%
“…Such secondary flows not only cause a reduction in the volumetric flow rate, but they can also cause the axial velocity field to be distorted with an outward shift of the contours of constant velocity. In addition, it is well known that the turbulent flow in straight noncircular ducts is characterized by the occurrence of secondary flows (see Jones 1965 andNakayama et al, 1983). A clear understanding of the evolution and consequences of the turbulent secondary flows in curved and straight ducts is, therefore, quite important from the design standpoint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, Gessner and Jones [1965] found that values of L/R of 160 (for a square duct) and 240 also gave fully developed conditions. Nezu and Rodi [1986] used L/R of 326 for their analyses in open channel flow.…”
Section: Measurement Locationsmentioning
confidence: 88%
“…Measurements to determine the orientation of the traces of turbulent-stress principal planes in ducts of non-circular cross-section were carried out by Gessner and Jones [5] and by Perkins [10]. The latter believed it reasonable to hypothesize that the direction with respect to which the turbulent shear-stress value in the cross-section appears to be maximum will always remain aligned to the isovels, even in the presence of secondary currents or of distortions in the flow field due to the shape of the contour.…”
Section: Introduction Les éCoulements Turbulentsmentioning
confidence: 99%